2010
DOI: 10.3109/00016481003621538
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of recurrent epistaxis: The experience of two metropolitan hospitals in Italy

Abstract: The patients' mean age was 58.7 years; the mean hospital stay was 2.97 days. In 42 cases (87.5%), cauterization of the sphenopalatine artery was performed, and 6 (12.5%) were subjected to anterior ethmoid artery treatment. Epistaxis control was achieved in 93% of cases; 3 patients had a recurrent nasal bleeding, and were treated with anterior nasal packing. Minor complications occurred in 27.1%. We achieved a shorter hospital stay compared with patients who underwent anteroposterior packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 15 publications
1
29
0
2
Order By: Relevance
“…Furthermore, additional three papers were obtained by hand‐searching. Finally, 33 full papers were included in the present study . These data are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, additional three papers were obtained by hand‐searching. Finally, 33 full papers were included in the present study . These data are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The pooled perioperative complication rate was 8.7% (95% CI, 4.9–15.1). The most frequent complication was nasal crusting, which occurred in either 21% or 8% . The second most frequent complication was acute sinusitis and nasal dryness: acute sinusitis occurred in 10% and severe nasal dryness occurred in 10% .…”
Section: Resultsmentioning
confidence: 99%
“…The traditional treatment strategy of posterior nasal packing has been largely replaced by the more effective and less morbid techniques of transnasal endoscopic sphenopalatine artery ligation (TESPAL) [1][2][3] and endovascular arterial embolization. [4][5][6] Furthermore, a recent study by Dedhia et al 7 suggested that TESPAL is the most cost-effective strategy compared with posterior nasal packing.…”
mentioning
confidence: 99%
“…Bu ru nun ko lay ula şı la bi len böl ge le rin de mey da na ge len ve ka na ma nın bol olma dı ğı du rum lar da epis tak si sin kon tro lün de en sık uy gu la nan yön tem lo kal ko te ri zas yon dur. [8][9][10][11][12][13] Kimya sal ya da elek tro ko te ri zas yon ya pı la bi lir. Kim yasal ko te ri zas yon gü müş nit rat çu bu ğu ile ya pı lır.…”
Section: Te Da Vi̇unclassified
“…[21][22][23][24][25][26] Tam po na rağ men de vam eden ka na ma lar da sfe nopa la tin ar ter ve an te ri or et mo i dal ar te rin en dos kopik ko te ri zas yo nu ya pı lır. 13 Sep top las ti, an te ri or ve 1. Has ta nın ha va yo lu, so lu nu mu ve do la şı mı kon trol edil me li 2.…”
Section: 2unclassified